Outcomes of the minimally invasive aortic valve replacement - M. A. Snegirev; A. A. Paivin; D. O. Denisyuk; N. E. Khvan; L. B. Sichinava; V. E. Sharafutdinov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to demonstrate clinical outcomes of minimally invasive aortic valve replacement (MIAVR).MATERIAL AND METHODS. We retrospectively analyzed surgical results of treatment of patients underwent isolated AVR in our Institution between 2006 and 2018. Overall number of operations was 122; 56 of patient were operated via upper ministernotomy approach. Preoperative characteristics were similar in both groups.RESULTS. In our series MIAVR procedures had prolonged CPB and aortic cross clamping time, what significantly contributed to the increase in manifestations of heart failure in the early postoperative period, but didn’t affect the perioperative mortality and major morbidity rates. MIAVR led to reduction in postoperative blood loss and perioperative red blood cell transfusion rate. Most severe complications occurred in frail patients older than 75 years, and in those with extensive aortic annular calcification.CONCLUSION. MIAVR was the safe and reproducible surgical intervention and rarely led to significant complications in low-risk patients. Prolonged CPB time adversely affected the frequency of significant complications, especially in elderly patients. Although, selected high risk patients might benefit with MIAVR.